Perancangan Strategy Maps dan Balanced Scorecard pada PT Bahtera Abadi Gas Gresik - Irfan Aulia Hoesaini (UNUSA Press, 2018)
Abstract: The growth of the business of gas industry in Indonesia make firm that deals with this industry will develop. Increase in the number of a company that produces gas trigger intense competition to gain customers that there is to consume gas. PT Bahtera Abadi Gas is one of the company that moves in the field of gas industry national scale. On the way various customers than any other company have been handled by PT BAG that majority exists in the region of east java. An intense competition in gain customers of the company between a gas that with each other to cause to compete with companies in providing a bargain price that low and improved service quality to win over the competition. With a bargain price that is very competitive, companies should do the efficiency and effectiveness of its production in the process so as to achieve the level of its optimum profit. In order to continue to compete, required managerial instrument that can help to formulate a strategy company in accordance with the vision, mission and objectives of the company that can be translated into the act of operational in clear and measurable accomplishment. In addition a strategy company in the level of implementation can be functioned as instrument of the measure- ment of performance management in addition to the goal is to investigate the effectiveness of the application of the strategy itself, also to control the performance management and minimize the potential there is the deception. The result of research shows that PT BAG having strategic objec- tives in map competition that is reflected in four perspective balanced scorecard. Strategic objec- tives financial perspective is utilization assets, cost efficiency, increase revenue. The purpose of from the perspective of a customer is customer satisfaction, customer retention, customer acquisi- tion. The purpose of internal from the perspective of a business process is of quality, delivery, healthy and safety work, develop sustainable relationship with supplier. From the perspective of the purpose of learning and growth is increase employee competency, increase productivity employee, recruit quality employee, improved teamwork, employee feedback systems, availability of infor- mation technology.